2013
DOI: 10.1002/jctb.4037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sub‐ and super‐critical CO2 pretreatment on conformation and catalytic properties evaluation of two commercial enzymes of CALB and Lipase PS

Abstract: BACKGROUND: It is vitally important to understand the effect of sub-/super-critical CO 2 pretreatment on enzyme conformation and its activity, which should improve the understanding of enzymatic biotransformation applications in nonaqueous media. This study evaluated the effect of sub-/super-critical CO 2 treatment, including pressure (6 and 10 MPa), exposure time (20, 30 and 150 min) and temperature (35 and 40 • C), on the conformation (e.g. 1D, 2D and 3D structures) and catalytic properties (e.g. residual ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…The enzyme activity of free enzymes after SC-CO 2 treatment was determined as the initial rate in the hydrolysis reaction of the olive oil triglycerides [12]. In a typical assay, 1 mL of enzyme preparation was added to the substrate, consisting on 4 mL of 10 % homogenized olive oil and 5 mL of 50 mM phosphate buffer pH = 7.0.…”
Section: Residual Enzyme Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…The enzyme activity of free enzymes after SC-CO 2 treatment was determined as the initial rate in the hydrolysis reaction of the olive oil triglycerides [12]. In a typical assay, 1 mL of enzyme preparation was added to the substrate, consisting on 4 mL of 10 % homogenized olive oil and 5 mL of 50 mM phosphate buffer pH = 7.0.…”
Section: Residual Enzyme Activitymentioning
confidence: 99%
“…It has been also proposed that SC-CO 2 may interact with hydrophobic tryptophan (Trp) and tyrosine (Tyr) residues in the enzyme structure during the treatment [10][11][12][13][14]. Liu et al [11] proposed that, below a pressure threshold that depends on the enzyme nature and on the experimental conditions, CO 2 can interact with Trp and Tyr residues by means of weak interactions, promoting conformational changes that lead to a more accessible active site.…”
Section: Residual Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Investigating the influence of temperature on the activity of two commercial immobilized lipases submitted to supercritical CO 2 , Oliveira et al [14] observed that at higher temperatures, up to 70 °C, the activity reductions were at least 8%. Liu et al [13] evaluated the effect of sub and supercritical CO 2 treatment, including pressure, exposure time and temperature on the residual activity of two commercial enzymes (Candida antarctica Lipase B (CALB) and lipase PS in solution). Differently from this work, the authors observed an increase of activity for both lipases after treatment with sub-and supercritical CO 2 , in which the highest residual activities obtained were 105% and 116% for CALB and lipase PS, respectively, at the same conditions (10 MPa, 40 °C and 30 minutes of exposure time).…”
Section: Effect Of Supercritical Carbon Dioxide On the Lipase Activitymentioning
confidence: 99%
“…The enzymatic activity was measured through the volumetric method, which is based on the titrimetric determination of the free acids released from triacylglycerols by lipase catalyzed hydrolysis [12,13]. About 5 ml of olive oil emulsion, water and arabic gum (7%), 2 ml of phosphate buffer pH 7.0 (0.1M) and 10 mg of enzyme were incubated for one hour in a shaker incubator (TE-421, Tecnal, Piracicaba-SP/Brazil) at 40 °C and 140 orbitals per minute (OPM).…”
Section: Lipase Activitymentioning
confidence: 99%